Weakening of functional corticomuscular coupling during muscle fatigue - Yang, Qi; Fang, Yin; Sun, Chang-Kai; Siemionow, Vlodek; Ranganathan, Vinoth K.; Khoshknabi, Dilara; Davis, Mellar P.; Walsh, Declan; Sahgal, Vinod; Yue, Guang H. (Brain research, 2009)
Recent research has shown dissociation between changes in brain and muscle signals during voluntary muscle fatigue, which may suggest weakening of functional corticomuscular coupling. However, this weakening of brain–muscle coupling has never been directly evaluated. The purpose of this study was to address this issue by quantifying EEG–EMG coherence at times when muscles experienced minimal versus significant fatigue. Nine healthy subjects sustained an isometric elbow flexion at 30% maximal level until exhaustion while their brain (EEG) and muscle (EMG) activities were recorded. The entire duration of the EEG and EMG recordings was divided into the first half (stage 1 with minimal fatigue) and second half (stage 2 with severer fatigue). The EEG–EMG coherence and power spectrum in each stage was computed. Results: The power of both EEG and EMG increased significantly while their coherence decreased significantly in stage 2 compared with stage 1 at beta (15–35 Hz) band. Despite an elevation of the power for both the EEG and EMG activities with muscle fatigue, the fatigue weakens strength of brain–muscle signal coupling at beta frequency band. Weakening of corticomuscular coupling may be a major neural mechanism contributing to muscle fatigue and associated performance impairment.